Perinatal mortality. Experience in the Guillermo Almenara Irigoyen National Hospital (1990-1997) - Alegría, Raúl (2015)
OBJETIVE. To report true and corrected perinatal mortality rates al GAINH. DESIGN. Restrospective study of clinical histories of dead newborn infants and fetal deaths occuring at the Obstetrical Service GAINH from January 1, 1990 through May 31 1997. Results are presented by statistical analysis. STTING. Obstetrical Service, Guillermo Almenara Irigoyen National Hospital. RESULTS. From 561 clinical histories of perinatal deaths we studied 330 death dating 28 gestational weeks on. Perinatal mortality rat was 10,6 x 1000 Inb and corrected perinatal mortality rate 5,6 x 1000 Inb, with increase during 1994 and 1995. Congenital malformations occurred in 18%. We correlated perinatal death with gestational age, weight and amniotic fluid characteristics. CONCLUSION. Introduction of fetal surveillance at the Obstetrical Service has decreased general perinatal mortality rate, not with standing after 1994 it has become an almost exclusive reference centar; consequently, 70% of pregnant women referred carry risk factors and morbility and mortality are higher than in a general hospital.